1691 Yılında Yazılmış Bir Şifalı Bitkiler Kitabına Dair - Demir, Nurettin (Gökkubbe, 2005)
Aşağıdaki yazıda Forschungs- und Landesbibliothek Gotha'da (Almanya), Doğu Yazmaları bölümü Persch Kataloğu T 122 numarada kayıtlı, 32 varaklık bir şifalı bitkiler kitabıdır. Çalışmada yazmanın yazılış tarihi, yazarı, yazılış sebebi, konusu, yazmada kayıtlı şifalı bitkilerin adları gibi tanıtıcı bilgiler verilecektir. The following study describes a thirty- two page manuscript, which is registered in the Pertsch Katalog, no. T122, the oriental section of Forschungs und Landesbibliothek Gotha, Germany. This study will provide some brief information about the date of the manuscript, its author, content, and aim, and the names of the medicinal plants listed in it.
About a Book Written 1691 an Medicinal Plants
Keywords: Türkçe Yazmalar; Şifalı Bitkiler; Halk Hekimliği; Ottoman Manuscript; Medicinal Plants; Popular Medicine